1999
DOI: 10.1016/s0002-9440(10)65322-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Transitional Cell Carcinogenesis Is Associated with Down-Regulation of NF1 Tumor Suppressor Gene in Vivo and in Vitro

Abstract: The NF1 gene product (neurofibromin) is known to act as a tumor suppressor protein by inactivating ras. The best documented factors involved in urinary bladder transitional cell carcinoma (TCC) are ras proto-oncogene activation and p53 suppressor gene mutations. This is the first study reporting alterations in NF1 gene expression in TCC. We examined NF1 gene expression in a total of 29 surgical urinary bladder TCC specimens representing grades 1 to 3 and in three cell lines , RT4 , 5637 , and T24 (representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…The absence of the NF1 inhibitory effect will favor increased cell proliferation, as found in the superficial tumor compartments of muscle-invasive TCC (Blanes et al, 1999). Likewise, Aaltonen et al (1999) have reported a decreased NF1 mRNA and protein levels in high-grade TCC, suggesting that alterations in NF1 gene expression may be involved in bladder carcinogenesis. On the other hand, we found TP53 abnormalities in 29 of 43 informative cases (67.4%), after screening two introns.…”
Section: Diaz-cano Et Almentioning
confidence: 97%
“…The absence of the NF1 inhibitory effect will favor increased cell proliferation, as found in the superficial tumor compartments of muscle-invasive TCC (Blanes et al, 1999). Likewise, Aaltonen et al (1999) have reported a decreased NF1 mRNA and protein levels in high-grade TCC, suggesting that alterations in NF1 gene expression may be involved in bladder carcinogenesis. On the other hand, we found TP53 abnormalities in 29 of 43 informative cases (67.4%), after screening two introns.…”
Section: Diaz-cano Et Almentioning
confidence: 97%
“…34,35 RNA was extracted from cultured cells using either Nucleospin RNA II total RNA isolation kit (Macherey-Nagel Inc., Easton, PA) or RNAzol B reagent (TelTest Inc., Friendswood, TX) according to manufacturer's instructions. RNA samples were treated with 5 U of DNase I (Roche) to eliminate possible contaminating DNA.…”
Section: Rna Extraction and Cdna Synthesismentioning
confidence: 99%
“…5,6 Furthermore, the levels of NF1 protein and/or messenger RNA have been reported to be altered in certain proliferative diseases, such as transitional cell carcinoma and psoriasis. 13,14 On the other hand, neurofibromas have been described to develop on locations of previous mechanical trauma. 7,8 Interestingly, recent results demonstrate up-regulation of NF1 gene expression in response to tissue trauma and suggest that a "second hit" in a form of somatic mutations in lesional neurofibromatosis cells is not necessarily a prerequisite for the development of neurofibromas.…”
Section: Commentmentioning
confidence: 99%